The soils of Bangladesh - Huq, S.M. Imamul; Shoaib, Jalal Uddin Md (World Soils Book Series, 2013)
This book presents a comprehensive overview of the soils of Bangladesh. It is compiled by authors with vast experience in soil related problems and potential mitigation approaches. It discusses the development of Soil Science as an individual discipline in a country with limited resources and where soil plays a pivotal role for the economy; the formation of different agro-climatic regions; and the effects of human-induced soil degradation and climatic change on its soils, geology and geomorphology and major soil types. It examines 'problem soils' and how they are managed, the scenario of soil fertility status, and land and crop management, as well as focusing on the future soils. Topics covered include: the history of soil research in Bangladesh; agro-climatic regions of Bangladesh; soil and climatic change, major soil types;  soil maps; soil properties; soil classification; soil fertility; land use and vegetation; land use changes; human-induced soil degradation; soil contaminants; and future soil issues. This book will be a valuable resource for researchers and soil science professionals.